Does it Matter if We Get It Right? Impact of Appropriateness of Empiric Antimicrobial Therapy Among Surgical Patients - Davies, Stephen W. (2014)
BACKGROUND: Previous studies have shown conflicting evidence regarding the impact of inappropriate, initial antibiotic therapy. The purpose of this study was to evaluate the impact of inappropriate, empiric antimicrobial therapy for the treatment of infection among surgical patients. HYPOTHESIS: Inappropriate, empiric antimicrobial therapy predicts increased mortality risk compared with appropriate therapy. METHODS: This was a retrospective analysis of a prospectively maintained database of all surgical patients admitted to a tertiary care center from 1996-2007 and treated for sepsis. “Appropriate” empiric antibiotic treatment was determined by sensitivity testing. Demographics and comorbidities, infection sites, infection organisms, and outcomes were compared between inappropriately and appropriately treated groups. Multivariable, log-binomial regression was performed. RESULTS: There were 2,855 patients (7,158 infectious episodes) identified by culture analysis as either appropriately or inappropriately treated. Three hundred seventeen (15%) inappropriately treated infectious episodes resulted in death compared with 718 (14%) of the appropriately treated infectious episodes. After adjusting for statistically significant variables, inappropriately treated episodes of infection were not found to be associated with an increased risk for mortality compared with appropriately treated episodes of infection (RR=1.0, 95%CI=0.99-1.02; p=0.36). CONCLUSION: Our study observed no difference in mortality between appropriately and inappropriately treated infections within a surgical population.